First-in-human study assessing safety, tolerability, and pharmacokinetics of 2-hydroxybenzylamine acetate, a selective dicarbonyl electrophile scavenger, in healthy volunteers - Lisa M. Pitchford; John A. Rathmacher; John C. Fuller; J. Scott Daniels; Ryan D. Morrison; Wendall S. Akers; Naji N. Abumrad; Venkataraman Amarnath; Patricia M. Currey; L. Jackson Roberts; John A. Oates; Olivier Boutaud (BMC, 2019)
Abstract Background 2-Hydroxybenzylamine (2-HOBA) is a selective scavenger of dicarbonyl electrophiles that protects proteins and lipids from being modified by these electrophiles. It is currently being developed for use as a nutritional supplement to help maintain good health and protect against the development of conditions associated with dicarbonyl electrophile formation, such as the cognitive decline associated with Mild Cognitive Impairment and Alzheimer's disease. Methods In this first-in-human study, the safety, tolerability, and pharmacokinetics of six ascending single oral doses of 2-HOBA acetate were tested in eighteen healthy human volunteers. Results Reported adverse events were mild and considered unlikely to be related to 2-HOBA. There were no clinically significant changes in vital signs, ECG recordings, or clinical laboratory parameters. 2-HOBA was fairly rapidly absorbed, with a tmax of 1-2 h, and eliminated, with a t1/2 of approximately 2 h. Both tmax and t1/2 were independent of dose level, while Cmax and AUC increased proportionally with dose level. Conclusions 2-HOBA acetate was safe and well-tolerated at doses up to 825 mg in healthy human volunteers, positioning it as a good candidate for continued development as a nutritional supplement. Trial registration This study is registered at ClinicalTrials.gov (NCT03176940).